2023
DOI: 10.1094/pdis-03-22-0454-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Zucchini Tigre Mosaic Virus Infecting Four Cucurbit Crops in China

Abstract: Cucurbits including ridge gourd (Luffa acutangula), Chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How), Trichosanthes anguina, and sponge gourd (L. cylindrica) are important vegetables in most Asian countries. The 90 viruses known to infect cucurbits include 15 species in genus Potyvirus. In October 2020, nine cucurbit samples with leaf distortion, blister and mottle were collected from the same field of Foshan City, Guangdong Province, China. All samples were tested by western blot with potyvirus-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, with the expansion of cultivation, various diseases have arisen, especially viral diseases, which have been a major factor restricting the yield and quality of chieh-qua in China. Diverse virus-like symptoms, including mosaic, interveinal chlorosis, mottling and leaf deformation, are frequently observed in chieh-qua; however, there has been limited research on sporadic chieh-qua samples and only four viruses have been reported: zucchini tigre mosaic virus (ZTMV, genus Potyvirus ), zucchini yellow mosaic virus (ZYMV, genus Potyvirus ), papaya ringspot virus (PRSV, genus Potyvirus ) and cucumber mosaic virus (CMV, genus Cucumovirus ) [ 6 , 7 , 8 ]. ZYMV, PRSV and CMV have been frequently identified in cucurbit vegetables in China [ 9 ], whereas ZTMV has only been discovered in China in recent years, with a potential risk to infect more cucurbit crops in the field [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the expansion of cultivation, various diseases have arisen, especially viral diseases, which have been a major factor restricting the yield and quality of chieh-qua in China. Diverse virus-like symptoms, including mosaic, interveinal chlorosis, mottling and leaf deformation, are frequently observed in chieh-qua; however, there has been limited research on sporadic chieh-qua samples and only four viruses have been reported: zucchini tigre mosaic virus (ZTMV, genus Potyvirus ), zucchini yellow mosaic virus (ZYMV, genus Potyvirus ), papaya ringspot virus (PRSV, genus Potyvirus ) and cucumber mosaic virus (CMV, genus Cucumovirus ) [ 6 , 7 , 8 ]. ZYMV, PRSV and CMV have been frequently identified in cucurbit vegetables in China [ 9 ], whereas ZTMV has only been discovered in China in recent years, with a potential risk to infect more cucurbit crops in the field [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, it is cultivated widely, particularly in the southern regions, where it has gained prominence and popularity among consumers. In previous study, we reported the natural occurrence of ZTMV in samples of snake gourd plants from Foshan City in Guangdong Province, China, that exhibited mottling and crinkling symptoms [9]. In this study, the infectious full-length cDNA clone of ZTMV infecting snake gourd (ZTMV-FS) was constructed, and its infectivity on cucurbit crops was examined.…”
mentioning
confidence: 99%
“…However, biological, serological and molecular biology studies suggest that it should be a distinct species within the genus Potyvirus [3]. To date, ZTMV has been reported across three continents, including Asia, Europe, and the Americas, as well as in some Caribbean and Indian Ocean islands [3][4][5][6][7][8][9]. The rst Chinese isolate of ZTMV was reported in 2014, and has since been recognized as a predominant pathogen impacting cucurbit production due to Author contributions Cuiji and Chengrong Nie conceived and designed the experiments.…”
mentioning
confidence: 99%
See 2 more Smart Citations